PENGARUH PEMBERIAN PUPUK NPK, ABMIX, DAN PUPUK KOMPOS CAIR MELALUI MEDIA TANAM AEROPONIK TERHADAP PERTUMBUHAN TANAMAN SELADA KERITING (Lactuca sativa L) - N Putri Sumaryani; Gek Wisky Ari (FPMIPA IKIP PGRI Bali, 2016)
The use of aeroponics system is one alternative for horticultural growing vegetables such as curly lettuce. This study used three types namely NPK fertilizer, AB mix and liquid compost. This study aimed to determine the effect of NPK fertilizer, ABmix and liquid compost through aeroponic growing media on plant growth curly lettuce (Lactuca sativa L) and to know which is better fertilizer for plant growth curly lettuce (Lactuca sativa L). The formulation of the hypothesis proposed in this study is the alternative hypothesis (Ha) which says that there is influence of NPK fertilizer, ABmix and liquid compost through aeroponic growing media on plant growth curly lettuce (Lactuca sativa L). This type of research experiments conducted with the use of a pattern of